LITERATUR REVIEW: HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN KEJADIAN DEPRESI PADA LANSIA USIA 60-74 TAHUN: LITERATUR REVIEW: HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN KEJADIAN DEPRESI PADA LANSIA USIA 60-74 TAHUN - Hadi, Saiful (LPPM STIKes Bahrul Ulum Jombang, 2022)
Depression is the most common mental problem in the elderly, when entering the elderly must experience loneliness because it is far from the child and left behind by a live partner, the disorder of depression in the elderly is rarely known by the elderly because many elderly people are not open with their family so that depression in the elderly is not recognized (under diagnosed) and untreated (under treated) which causes a third of sufferers to die. Factors causing depression in the elderly include biological factors, psychology, chronic stress, drug use. Researchers wanted to analyze the Relationship between Family Support and Depression Rates in the elderly. Older people will become particularly susceptible to health problems, including depression caused by stress in the face of life-changing changes related to the so-called golden year. Life changes include retirement, illness or physical disability. The purpose of this study is to find out the relationship of family social support with the incidence of depression in The Age of 60-74 years. The study design literature studies the relationship of family support with depression rates in the elderly. This research can be concluded that the relationship of family social support with the incidence of depression in the Elderly ages 60-74. Can provide education and strong information for the elderly and families such as, lifestyle, lifestyle and daily adaptation, strength of personality and interests